2014
DOI: 10.1071/an14355
|View full text |Cite
|
Sign up to set email alerts
|

Metabolisable energy requirements for maintenance and gain of liveweight of Bali cattle (Bos javanicus)

Abstract: A series of liveweight gain (LWG), feed and water intake and digestibility experiments were conducted across eastern Indonesia. Thirty-six datasets of LWG, feed and water intake, and diet characteristics were used to determine the nutritional requirements of growing Bali cattle fed a wide range of diets that varied in crude protein content and apparent dry matter digestibility. Regression of average daily LWG against estimated metabolisable energy (ME) intake was conducted, and the ME requirements for maintena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…The ME requirement for maintenance (ME m ) was estimated by regressing ADG on daily ME intake (MEI), as ADG is an indirect measure of energy retention, and the MEI at “ADG = 0” was shown to estimate energy requirements accurately ( Quigley et al., 2014 ; Liu et al., 2019 ). The regression equation took the following form: ADG (g/d) = a MEI (MJ/kg BW 0.75 per d) + b .…”
Section: Methodsmentioning
confidence: 99%
“…The ME requirement for maintenance (ME m ) was estimated by regressing ADG on daily ME intake (MEI), as ADG is an indirect measure of energy retention, and the MEI at “ADG = 0” was shown to estimate energy requirements accurately ( Quigley et al., 2014 ; Liu et al., 2019 ). The regression equation took the following form: ADG (g/d) = a MEI (MJ/kg BW 0.75 per d) + b .…”
Section: Methodsmentioning
confidence: 99%
“…The LWG of cattle recorded in this experiment was still below the highest values recorded for Bali bulls. Higher growth rates of 0.56-0.61 kg/d were reported by Quigley et al, (2014) when a Leucaena-based diet was supplemented with energy sources (maize grain or rice bran) at about 40% of diet. Dahlanuddin et al, (2018) also reported a higher liveweight gain of 0.66 kg/d for similar class of Bali bulls fed Leucaena and supplemented with maize grain at 40% of diet.…”
Section: Discussionmentioning
confidence: 89%
“…The increase in ADG in this study was in line with the increase in protein intake and metabolic energy retention (Table 2). Quigley [19] found that the metabolisable energy required for maintenance is 0.47 MJ EM/kg body weight 0.75 for young male Bali cattle. Poppi [20] recommends that the growth rate of beef cattle can be increased if metabolasble energy intake meets animal needs.…”
Section: Nutrition Content Of Feedstuffsmentioning
confidence: 99%